2020
DOI: 10.21203/rs.3.rs-59522/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Infant Sex Modifies Associations Between Placental Malaria and Risk of Malaria in Infancy

Abstract: Background Placental malaria (PM) has been associated with a higher risk of malaria during infancy. However, it is unclear whether this association is causal, and is modified by infant sex, and whether intermittent preventive treatment in pregnancy (IPTp) can reduce infant malaria by preventing PM.MethodsData from a birth cohort of 656 infants born to HIV-uninfected mothers randomized to IPTp with dihydroartemisinin-piperaquine (DP) or sulfadoxine-pyrimethamine (SP) was analyzed. PM was categorized as no PM, a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Infant sex appears to modify this risk. In Uganda, malaria incidence in infancy was higher in male, but not female, infants of women with severe placental malaria [adjusted incidence rate ratio (IRR) 2.17, 95% CI 1.45, 3.25] [5].…”
Section: Risk Of Malaria In Infancymentioning
confidence: 99%
See 1 more Smart Citation
“…Infant sex appears to modify this risk. In Uganda, malaria incidence in infancy was higher in male, but not female, infants of women with severe placental malaria [adjusted incidence rate ratio (IRR) 2.17, 95% CI 1.45, 3.25] [5].…”
Section: Risk Of Malaria In Infancymentioning
confidence: 99%
“…These cells express the parasite protein VAR2CSA on their surface, which binds to chondroitin sulfate A (CSA) on placental cells. The consequences of placental malaria can include severe maternal anemia, miscarriage, stillbirth and perinatal mortality [2 ▪ ,3 ▪ ], premature delivery, small for gestational age (SGA) and low birth weight (LBW; birth weight <2500 g) [4], and altered risk of malaria in infancy [5]. Each year, ∼900 000 babies are born with LBW attributable to malaria in pregnancy, and ∼100 000 infants die.…”
Section: Introductionmentioning
confidence: 99%
“…Although information on gender is routinely collected from patients presenting to public health facilities, stratification of malaria surveillance data by gender is rarely done. Studies have suggested differences may exist between females and males in the risk of infection and disease, but few studies have evaluated gender differences in the context of routine malaria surveillance data from public health facilities [3,4]. An appreciation of gender difference in malaria burden would be important for improving the understanding of factors that may influence susceptibility to malaria, case management practices, and targeting control interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Most data available on associations between gender and malaria come from cohort and cross-sectional studies [3,4,13,14], which may not be representative of patients who seek care at public health facilities and contribute to routine malaria surveillance data through HMIS. In Uganda, an enhanced health facility-based malaria surveillance system has been established at sentinel public health centres to provide high quality data around the country.…”
Section: Introductionmentioning
confidence: 99%